Single nucleotide polymorphism rs4648298 in miRNAs hsa-miR21 and hsa-miR590 binding site of COX gene is a strong colorectal cancer determinant - Mosallaei, Meysam (J Gastrointest Oncol, 2018)
BACKGROUND: Genetic determinants are considered as driving forces in development colorectal cancer (CRC), a malignancy that ranks as the second cause of cancer death in the world. Single nucleotide polymorphisms (SNPs), are considered as the main genetic factor in cancers susceptibility. MicroRNAs are critical players in posttranslational gene regulation by binding to their specific recognition sequences located at 3' untranslated region (UTR) of mRNAs. In present study we have elucidated the role of 9,850 A > G (rs4648298), in development of sporadic CRC in Iranian population. METHODS: A case-control study using 88 CRC patients and 88 noncancerous counterparts was undertaken in order to determine rs4648298 genotypes using polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP) method. Also, a meta-analysis was performed based on 9 articles accessed via the MEDLINE, Cochrane review, Google Scholar and Scopus databases. RESULTS: AA genotype was determined to be associated with significant decreased risk of CRC in our study population [odds ratio (OR) =0.14; 95% confidence interval (CI), 0.05–0.34; P<0.001]. In a meta-analysis on 6 risk estimates for the AG versus AA genotype, we found a significant inverse association between AG SNPs and risk of gastric adenocarcinoma, CRC, breast cancer and prostate cancer (OR =0.86; 95% CI, 0.76–0.98; P<0.02). CONCLUSIONS: Our results suggest significant correlation between rs4648298 polymorphism and CRC risk in Iranian population.